The agricultural law of the EU - Barents, R. (European monographs ;, 2022)
The Agricultural Law of the EU', currently in its second edition, is an updated version of the distinguished work on European Union (EU) agricultural law, and it lays emphasis on the radical changes that have brought about the progressive development of the common agricultural policy to embrace the food chain as a whole. Albeit the new edition retains the same objective and methodology, the author presents a fresh overview of the field as it now exists, including the impact of the latest reform measures up to 2021 and their ramifications for the future.